Investigating the Impact of Surfactant and Cosolvent on the Polyphenolic Content in Arumanis Mango Leaf Extract (Mangifera indica L.) - Fatimah, Siti Fatmawati; Farida, Verda; Nuari, Yudha Rizky; Viviandhari, Daniek; Pertiwi, Deasy Vanda (Fakultas Farmasi Universitas Andalas, 2024)
The leaf of Mangifera indica L. contains flavonoids and mangiferin which showed positive effects on wound healing of diabetic ulcer. The used of suitable surfactant and co-solvent is required to ensure the high solubility of the active pharmaceutical ingredient (API), thereby optimizing the efficacy. This study aims to determine the ideal surfactant and cosolvent for a thermosensitive hydrogel formula of Mangifera indica leaf ethanol extract. The leaf was fextracted by maceration using 70% ethanol then determined for moisture content. The extract was prepared for solubility tests of flavonoid and mangiferin on surfactants (Kolliphor® EL, Tween® 20, Tween® 80, Miranol® C2M) and co-solvents (Glycerin, PEG 400, and transcutol). Methods for total flavonoids content were Spectrophotometry UV-Vis and mangiferin with RP-HPLC method. The moisture content in the extract is 8.590 ± 0.754%. The surfactant demonstrating the highest capability in flavonoid dissolution is Tween 20 (1863.750 ± 0.838 µgQE/g extract), followed by Tween 80, Kolliphor EL, and Miranol C2M. In the context of co-solvents, PEG 400 (1309.583 ± 0.292 µgQE/g extract) show superior flavonoid dissolution capability, with glycerin and Transcutol following in descending order. Tween 20 and Tween 80 exhibite comparable efficacy in mangiferin dissolution, followed by Miranol C2M and Kolliphor EL. Among co-solvents, Transcutol demonstrate the highest aptitude for mangiferin dissolution, succeeded by PEG 400 and glycerin. This study indicates Tween 20 is a preferable surfactant and PEG 400 was considered as co-solvent to be further used in a thermosensitive gel formula for diabetic ulcer.